Extraskeletal myxoid chondrosarcoma in the pelvis successfully treated with proton beam radiotherapy. Issue 1 (31st January 2023) - Honda, Yosuke; Katagiri, Hirohisa; Onoe, Tsuyoshi; Aramaki, Takeshi
Abstract : The standard treatment for extraskeletal myxoid chondrosarcoma is wide excision. However, extraskeletal myxoid chondrosarcoma is often located in the deep layers of the extremities and pelvis, so functional impairment due to wide resection is unavoidable in many cases. In addition, the efficacy of radiotherapy and chemotherapy has not been defined, so no treatment method is established for unresectable cases. Here we report a case involving a man in his late 60s with extraskeletal myxoid chondrosarcoma of the pelvis who responded to proton beam radiotherapy with intra-arterial chemotherapy and did not require surgery. The patient maintained a complete response for more than 7 years. The findings from this case suggest that definitive irradiation can be an alternative to wide resection for cases of extraskeletal myxoid chondrosarcoma in which severe disability cannot be avoided after resection or when the tumour is inoperable due to its size and location.